2003
DOI: 10.1034/j.1600-0420.2003.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related macular degeneration: filter lenses help in certain situations

Abstract: ABSTRACT.Purpose: To investigate the ability of different filter lenses to enhance the contrast sensitivity of patients with age-related macular degeneration (AMD). Methods: A total of 32 patients with non-exudative AMD and no other significant eye diseases underwent the study tests using their optimal correction. We used Hyva¨rinen's contrast sensitivity tests with 100%, 10%, 5%, 2.5% and 1.25% charts. All the tests were made without filter lenses and with the Corning 527 and LVI 527 lenses. Results: With the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
0
11
0
2
Order By: Relevance
“…Since the RBANS is considered a screening measure, and as such may be administered at bedside or within a patient's room on a regular basis, light levels at the lower end of the range would exaggerate the influence of diminished CS. In addition, given the inherent difficulty of improving poor CS in individuals (Langagergaard et al, 2003), concentrating on enhancing the environmental setting may provide the maximal opportunity to insure a basic level of performance. It may also be beneficial to screen individuals for reduced CS as a precaution, particularly in light of individuals' relatively low level of accuracy when reporting their own vision (Friedman et al, 1999;Rubin et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Since the RBANS is considered a screening measure, and as such may be administered at bedside or within a patient's room on a regular basis, light levels at the lower end of the range would exaggerate the influence of diminished CS. In addition, given the inherent difficulty of improving poor CS in individuals (Langagergaard et al, 2003), concentrating on enhancing the environmental setting may provide the maximal opportunity to insure a basic level of performance. It may also be beneficial to screen individuals for reduced CS as a precaution, particularly in light of individuals' relatively low level of accuracy when reporting their own vision (Friedman et al, 1999;Rubin et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Despite the importance of CS, it is not consistently assessed formally in ophthalmologcal examinations (Bass et al, 1995), thus individuals may be unaware of declines in their ability. While visual acuity is relatively easy to correct for through the use of refractive lenses, decreased CS cannot be directly compensated for except through increased illumination (Langagergaard et al, 2003;Peli, Goldstein, Young, Trempe, & Buzney, 1991). Based on these population-based studies, there is clearly potential for an elderly individual to be adversely affected by reduced visual ability within the context of a neuropsychological evaluation, despite the examiner taking precautions such as asking about diagnosed visual dysfunction and requesting that an individual wear their corrective lenses during testing.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…This means that the results we have obtained in this study using coloured light filter overlays cannot easily be compared with those from other studies that used spectacle‐mounted light filters (Eperjesi et al 2004; Langagergaard et al 2003).…”
Section: Discussionmentioning
confidence: 85%
“…Several studies have assessed the effect of spectacle‐mounted short wavelength absorbing filters (often termed blue‐blockers) on visual performance in low vision. Some have reported a subjective preference for yellow and orange filters (Hoeft & Hughes 1981; Morrissette et al 1984; Maino & McMahon 1986; Provines et al 1997), while others have demonstrated objective improvements in visual performance (Hellinger 1983; Lynch & Brilliant 1984; Tupper et al 1985; Maino & McMahon 1986; Zigman 1990; Frennesson & Nilsson 1993; Wolffsohn et al 2002; Langagergaard et al 2003) and reading performance (Eperjesi et al 2004). See Eperjesi et al (2002) for a review.…”
Section: Introductionmentioning
confidence: 99%